Perception of colorscape in Naghsh-e-Jahan Square (Isfahan Iran) - Gholipour, Maryam Mohammad; Soomro, Ali Raza (2015)
Colors in Naghsh-e-Jahan Sq (one of the popular urban spaces in the world); which was built in Safavid dynasty, impact on people due to the approximately 50 interviews that were asked from visitors about their perception in 2014. According to the final results of interviews, the dominant color in this urban spaces was blue and it was recorded as a proper color for this Square while, the groups of Interviewees were from different countries and various cultures. Although this site was built around 400 years ago the percept results shows that color was spotted in building environment. So, in this research the Specifications of asked group and their percept will introduce.